Dissemination of The Importance of Community Participation with Clean and Healthy Living Behaviors Habits (PHBS) in Environment- Based Disease Prevention Efforts - Irfan, Asep; Darwel; Suksmerri (POLTEKKES KEMENKES PADANG, 2024)
Community participation is needed in a development program, because the success of the program is closely related to community participation in running a program, including the implementation of PHBS. Environment-based diseases always occupy the top 10 diseases reported by health centers in Indonesia. Clean and healthy living behavior (PHBS) of the community is expected to prevent environment-based diseases. The household environment is a unit that is very instrumental in the implementation of PHBS habits so that dissemination to the community, especially housewives on the importance of PHBS as an effort to prevent environment-based diseases. Cases of environment-based diseases, especially diarrhea, pulmonary TB, and dengue fever in Padang City are still high. The Monographic Book Dissemination activity aims to upload public awareness by inviting community leaders, especially in three locations, Nanggalo, Kuranji and Koto tangah, starting from the ranks of the sub-district office, Kelurahan, teachers, youth, health cadres and housewives on the importance of clean and healthy living behavior in the family environment in preventing environment-based diseases. The activity was carried out in the form of presentations, inviting resource persons from environmental health experts, and distributing Monographic books